Bioactive injectable mucoadhesive thermosensitive natural polymeric hydrogels for oral bone and periodontal regeneration - El-Nablaway, Mohammad; Rashed, Fatema; Taher, Ehab S.; Atia, Gamal A.; Foda, Tarek; Mohammed, Nourelhuda A.; Abdeen, Ahmed; Abdo, Mohamed; Hînda, Ioana; Imbrea, Ana-Maria; Taymour, Noha; Ibrahim, Ateya M.; et al. (Frontiers in Bioengineering and Biotechnology, 2024)
Periodontitis is an inflammation-related condition, caused by an infectious microbiome and host defense that causes damage to periodontium. The natural processes of the mouth, like saliva production and eating, significantly diminish therapeutic medication residency in the region of periodontal disease. Furthermore, the complexity and diversity of pathological mechanisms make successful periodontitis treatment challenging. As a result, developing enhanced local drug delivery technologies and logical therapy procedures provides the foundation for effective periodontitis treatment. Being biocompatible, biodegradable, and easily administered to the periodontal tissues, hydrogels have sparked substantial an intense curiosity in the discipline of periodontal therapy. The primary objective of hydrogel research has changed in recent years to intelligent thermosensitive hydrogels, that involve local adjustable solgel transformations and regulate medication release in reaction to temperature, we present a thorough introduction to the creation and efficient construction of new intelligent thermosensitive hydrogels for periodontal regeneration. We also address cutting-edge smart hydrogel treatment options based on periodontitis pathophysiology. Furthermore, the problems and prospective study objectives are reviewed, with a focus on establishing effective hydrogel delivery methods and prospective clinical applications.